(untitled) (Jagannath University Journal of Life and Earth Sciences, 2024)
A survey was conducted on some vegetable farmers from a few selected vegetable growing areas in Bangladesh to know their social aspects, pesticide knowledge, practices, safety measures, resources and effects of pesticides. A survey questionnaire was developed and sent to 90 randomly selected vegetable farmers to determine to what extent they used pesticides. Almost 87% of the farmers’ stored pesticides in their houses without safety consideration but only about 13% used special storage. About 78.7% of farmers never read the label before applying pesticides. The most protective clothes reported by the farmers were nose masks (18.2%), and about three-fourths (71.7%) of them did not use any protective clothing. The majority (61.8%) of the farmers threw away their empty containers, and only 16.9% burned them. The majority of farmers (92.1%) applied pesticides as both curative and preventive measures. Almost all farmers reported that infested pests were identified by themselves by observing damage to flowers & fruits (86.5%) and leaves & green parts (13.5%). Most of the farmers (64%) selected pesticides for controlling pests by themselves, and 28.1% with the help of experienced farmers. Nearly 45.0% of respondents have moderate knowledge, and 44.8% have good knowledge in pesticide application and management. The most common pesticide related illnesses and injuries reported by respondents were headache/dizziness (44.9%), weakness (33.7%), stomach cramps (29.2%), and blue-red vision (16.9%). Only 23.6% of farmers observed that pesticides decrease plant yield, and 18.0% of farmers knew that pesticides destroy soil microorganisms. As the environment and human health were poorly considered, only 19.1% of respondents were bio-pesticides, 4.5% were organic pesticides, 2.2% were non-persistence pesticides, and 2.2% were natural enemy users. Respondents have very poor knowledge about modern pest control methods like beneficial microorganisms (4.7%), beneficial insects (3.5%), biological control of pests (3.5%), IPM (2.3%), SIT (1.2%), and GMO crops (1.2%). Farmers’ age was correlated negatively with education (r = -0.380) and positively with experience (r = 0.909, P < 0.01). Pesticide related illness and injuries had a significant correlation with age (r = 0.465) and experience (r = 0.395). Jagannath University Journal of Life and Earth Sciences, 9(2): 111–124, 2023 (December)